Penerapan Manipulating Pleats Pada Busana Pesta Dengan Tema Exotic of Palm - Devitriana Devitriana; Indarti Indarti (Universitas Negeri Surabaya, 2025)
This study aims to describe the process of applying pleats as decoration to evening wear with an exotic palm theme. This theme is highlighted by the choice of a sage and armpit color palette, where the colors provide the exotic beauty of tropical palm trees, explored through shape, texture, and color translated into fashion design. This study uses the FEA Consumer Need Model method from Orzada & Kallal (2021), which consists of six stages: problem identification, initial ideas, design refinement, prototype development, evaluation, and implementation. In the problem identification stage, the need for aesthetic innovation in party wear that is not only visually appealing but also functional and expressive. The initial idea was developed based on the characteristics of palm trees and pleat manipulation techniques. Refinements were made by selecting materials, colors, and design details that match the theme. Fashion prototypes were developed and tested through visual and functional evaluations. The results show that pleat manipulation techniques are able to create party wear that is aesthetic, expressive, and relevant to the needs of modern consumers. This study contributes to the development of fashion design based on textile exploration and a strong thematic approach.